MPC as a tool for sustainable development integrated policy assessment - Kouvaritakis, B; Cannon, A; Couchman, P (2006)
A recent stochastic and multiobjective formulation based on static open-loop optimization has laid the foundations of a quantitative approach to sustainable development policy assessment. Here, the connections between such an approach and model predictive control are explored, and a reformulation that introduces dynamics and addresses closed loop performance and stability is proposed. The approach has wide applicability but it is hoped that it will provide sustainable development practitioners in particular with new insights. © 2006 IEEE.